Intracranial meningiomas: an update of the 2021 World Health Organization classifications and review of management with a focus on radiation therapy - Yarabarla, Varun; Mylarapu, Amrutha; Han, Tatiana J.; McGovern, Susan L.; Raza, Shaan M.; Beckham, Thomas H. (Frontiers in Oncology, 2023)
Meningiomas account for approximately one third of all primary intracranial tumors. Arising from the cells of the arachnoid mater, these neoplasms are found along meningeal surfaces within the calvarium and spinal canal. Many are discovered incidentally, and most are idiopathic, although risk factors associated with meningioma development include age, sex, prior radiation exposure, and familial genetic diseases. The World Health Organization grading system is based on histologic criteria, and are as follows: grade 1 meningiomas, a benign subtype; grade 2 meningiomas, which are of intermediately aggressive behavior and usually manifest histologic atypia; and grade 3, which demonstrate aggressive malignant behavior. Management is heavily dependent on tumor location, grade, and symptomatology. While many imaging-defined low grade appearing meningiomas are suitable for observation with serial imaging, others require aggressive management with surgery and adjuvant radiotherapy. For patients needing intervention, surgery is the optimal definitive approach with adjuvant radiation therapy guided by extent of resection, tumor grade, and location in addition to patient specific factors such as life expectancy. For grade 1 lesions, radiation can also be used as a monotherapy in the form of stereotactic radiosurgery or standard fractionated radiation therapy depending on tumor size, anatomic location, and proximity to dose-limiting organs at risk. Optimal management is paramount because of the generally long life-expectancy of patients with meningioma and the morbidity that can arise from tumor growth and recurrence as well as therapy itself.